Caribbean hoops : the development of West Indian basketball - Mandle, Jay R. (Caribbean studies, 1994)
The success of Caribbean basketball, the region's fastest growing sport, has been accompanied by prestige, opportunity, and frustration. The players' vision of their sport is the subject of this major study. Caribbean Hoops analyzes the sport's development, its strengths in voluntarism and commercialism as modes of organization, its special problems for referees, its political significance, and its methods of governance. Written in an informal style, the book is rigorous in its application of theory and convincing in its conclusions about the sport's problems and prospects. Engaging and topical, Caribbean Hoops presents a unique viewpoint on a growing, influential athletic and cultural phenomenon.